Social functioning impairment in patients with schizophrenia spectrum disorders and various contents of delusional ideas of influence - Pyliagina, Галина; Zahariichuk, Ольга (Psychosomatic Medicine and General Practice, 2025)
Background. Significant impairments in social functioning (SF) in patients with schizophrenia spectrum disorders (SSDs) are determined by many factors. One of them is the impact on patients of delusional ideas of influence (DIdInf) , which are a very common clinical feature of SSDs. Objective. To investigate the peculiarities and severity of SF disturbances in patients with SSDs and DIdInf with different content. Materials and Methods. There were 166 patients with various types of SSDs aged 18–55 examined and divided into two groups of 83 patients each. The first group consisted of 31 men (37.3%) and 52 women (62.7%) who revealed mystical-fantastic content in their DIdInf; the second group consisted of 48 men (57.8%) and 35 women (42.2%) with everyday-life domestic content of DIdInf. It was used clinical-psychopathological examination and psychodiagnostics of SF disturbances for all participants using the Global Assessment of Functioning (GAF) and the Social Functioning Assessment (PSP) scales. Results. It was found that the content of DIdInf plays a significant role in the nature and severity of SF disturbances. Statistically significant differences were found between patient groups depending on the content of DIdInf in relation to age, onset and course of the disorder, as well as the characteristics of SF disturbances. Conclusions. Taking into account the content's specific features of DIdInf in patients with SSDs and their impact on the nature and severity of SF disturbances is an important component for improving rehabilitation programmes and individualising approaches to the treatment of this patients. Keywords: diagnostics of mental disorders, mental health assessment, psychodiagnostics study; schizophrenia spectrum disorders, delusional ideas of influence with mystical-fantastic and everyday-life domestic content; evaluation of social functioning impairments. УДК 616.89-008.444-02:616.895.8-05-07:159.923:159.955